PARAMETER GENETIK TANAMAN AREN (Arenga pinnata L.) - Sakka Samudin; Muhammad Salim Saleh (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The aims of the experiment were to determine the coefficient of genetic diversity, heritability and correlation between these characters. The experiment was conducted in Palolo District of Donggala and Lore Regency of Poso, Central Sulawesi from May to August 2006.  The experiment used a Randomized Block Design with five replicates.  The treatment was six different villages: Baku-bakulu, Wuasa, Sigimpu, Bobo, Batumaeta and Winoanga, therefore, there were 30 experimental units used.  The results of the experiment indicated that 11 characters showed a large diversity coefficient while the other six characters had a small coefficient.  Plant height and leaf midrib length had a small heritability value while 15 other characters had a moderate value.  Such characters as plant height, leaf midrib length, first formed female spadix length, length of female spadix, twist of female spadix stalk, number of fruit, length of first formed male spadix, length of male spadix, length of male spadix stalk and twist of male spadix stalk could be used as indicators for indirect selection to enhance palm sap yield.